The Analysis of Macroeconomic and Microeconomic Factors in Non-Performing Financing of Sharia Bank in Indonesia - Yolanda Fransiska; Pani Akhiruddin Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to analysis of macroeconomic and microeconomic factors in non-performing financing of Sharia Bank in Indonesia. Inflation and the BI7DRR are macroeconomic factors. CAR and BOPO are indicators of microeconomic factors. NPF is a problematic financing indicator. Research methods with quantitative methods described in multiple linear regression analysis models. The population is obtained from the Bank Indonesia and Financial Ratios of Sharia Commercial Banks through the Sharia Indonesia Banking Statistics of the Financial Services Authority. The data is secondary in the form of monthly data for the period January 2018 to November 2022, so that a sample of 59 data was obtained for further analysis. Sampling techniques nonprobability by means of purposive sampling. The results of the study are as follows: (1) The estimation model shows an R2 value of 0,738 which represents the value of the coefficient of determination. This means that 73,80% of the dependent variable variation is able to be explained by the independent variables in this model. The remaining 26,20% is explained by other causes that are not included in the model; 2) The regression model on the independent variable simultaneously influence the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (3) This research produced output that the influential and significant ones are Inflation and BI7DRR as macroeconomic factors that can be used to analysis non-performing financing of Sharia Bank in Indonesia. This research also produced an output that CAR and BOPO have no influential as microeconomic factors that cannot be used to analysis non-performing financing of Sharia Bank in Indonesia. Although CAR and BOPO the results are significant.